Optimalisasi Peran Perpustakaan Sebagai Sumber Belajar Melalui Pendidikan Pemustaka - Jurianto Jurianto (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2017)
The Academic Library has a very important role in the learning process. The Academic library becomes the center of learning resources as well as the information center. In performing its duties college libraries not only provide learning resources, but also have to empower users through user education. With user education, it is expected that users are able to use various facilities owned by the library and have various skills in identifying, locating, searching, and utilizing information to disseminate information. User education should be structured based on needs analysis so as to meet the skills and information needs required by the user.